Perceptual narrowing in the context of increased variation: Insights from bilingual infants. (20th September 2013) - Byers‐Heinlein, Krista; Fennell, Christopher T.
ABSTRACT: Human infants become native‐language listeners through a process of perceptual narrowing. Monolingual infants are initially sensitive to a wide range of language‐relevant contrasts. However, as they mature and gain native‐language experience, their sensitivity to nonnative contrasts declines. Here, we consider the case of infants growing up bilingual as a window into how increased variation affects early perceptual development. These infants encounter different meaningful contrasts in each of their languages, and must also attend to contrasts that occur between their languages. Bilingual infants share many classic developmental patterns with monolinguals. However, they also show unique developmental patterns in the perception of native distinctions such as U‐shaped trajectories and dose–response relationships, and show some enhanced sensitivity to nonnative distinctions. Analogous developmental patterns can be observed in individuals exposed to two nonlinguistic systems in domains such as music and face perception. Some preliminary evidence suggests that bilingual individuals might retain more sensitivity to nonnative contrasts, reaching a less narrow end state than monolinguals. Nevertheless, bilingual infants do become perceptually specialized native listeners to both of their languages, despite increased variation and differing patterns of perceptual development in comparison to monolinguals . © 2013 Wiley Periodicals, Inc . Dev Psychobiol 56: 274–291, 2014.